Free Fibular Flap in Mandibular Defect Reconstruction in Perspective of a Tertiary Care Hospital of Bangladesh - Kabir, Mohammad Iqbal; Rahaman, Muhammad Mizanur; Rabby, Md Atiqul Islam; Hasan, Shamim; Rob, Md Abdur; Chowdhury, Golam Mohiuddin; Haider, Ismat Ara (Medicine Today, 2019)
Introduction:The principal objectives of reconstruction after mandible resection are to restore physiological articulation, chewing, swallowing functions and esthetics of the patient. Metal plate and bone graft are usually used to achieve this purpose.From the point of view of bone resorption and augmented exposure to infection, free vascularized fibular flap (FFF), comprising alive bone, have shown a lower infection rate and high rate of success. Materials and Methods: The study population of this clinical report included undertaking mandibular reconstruction by transplantation of a free vascularized fibular flap at the Department of Oral and Maxillofacial Surgery at the Dhaka Dental College between May 2014 to November 2014. The factors consider for studying were as following- age, sex, primary disease , period of reconstruction, mandibular defect classification, mandible resection range, height of reconstructed mandibular bone, number of locations of mandible osteotomy, vascular anastomosis and complication. Results: Primary disease comprised one was ameloblastoma, one was recurrent ameloblastoma, and another was post-surgical facial deformity. According to the CAT classification body was the most commonly observed defect. All mandibular bones were left as single barrel. There were 2 cases of primary reconstruction and 1 of secondary reconstruction. Free fibular flap ranges from 12-18 cm. No postoperative complications were seen in any case. Conclusion: Vascularized fibular flap is good choice in wide-range faults hard to fill with an iliac block graft. Further studies including greater samples of patients undertaking fibular bone transplantation are needed to comparatively investigate its merits in more detail. Medicine Today 2019 Vol.31(2): 80-84